DIGITALIZATION AND DECARBONIZATION: ASPECTS OF SYNERGY IN THE EU INDUSTRIES - Ірина Максимова; Віталіна Куриляк (Економіка та суспільство)
The article explores the synergy between digitalization and decarbonization within the EU’s most carbon-intensive industries, with a particular focus on the green transition in the energy sector. The study examines the EU’s twin transition experience, highlighting the role of digital technologies as key drivers for a climate-neutral economy. Through an analysis of digital applications in energy and industrial production, the authors identify crucial digital solutions, including smart grids, AI, and big data, that accelerate decarbonization efforts. The article provides a comprehensive review of EU initiatives, showcasing successful examples of green and digital integration to reduce greenhouse gas emissions. Key areas of synergy between decarbonization and digitalization are emphasized, illustrating how the twin transition not only reduces emissions but also improves resource efficiency and resilience to climate-related challenges. The paper organizes digital practices across EU sectors and proposes models that may serve as frameworks for building a global climate-neutral economy.